Salt concentration effects on mechanical properties of LiPF6/poly(propylene glycol) diacrylate solid electrolyte: Insights from reactive molecular dynamics simulations. (10th December 2016) - Verners, Osvalds; Thijsse, Barend J.; van Duin, Adri C.T.; Simone, Angelo
Abstract : Highlights: correlation between mechanical properties and LiPF6 concentration is observed reduced strength and failure strain at increasing LiPF6 concentrations is observed correlation between LiPF6 concentration and ion clustering is confirmed Abstract: Multifunctional composites with load carrying and electrical energy storage capability are relevant for diverse applications. Due to often conflicting requirements for improving both functions, extended knowledge of mechanical material properties is crucial. This study analyzes the mechanical properties of a solid polymer electrolyte material for structural battery applications by means of reactive molecular dynamics simulations. Specifically, conditions for improving load carrying capacity are considered. With the aim of determining optimum salt concentration for mechanical performance, we report the findings on the electrolyte salt effects on the polymer's mechanical properties, including hydrostatic failure behavior. The findings indicate a possibility for stiffness improvement above a threshold concentration value, as well as significant differences in isotropic compression and expansion failure behavior. In isotropic expansion and shear, small failure strength and failure strain reduction at increasing salt concentration is observed. In hydrostatic compression no material failure is observed up to 10 GPa. As a part of the molecular dynamics potential validation, the observed differences between references and test simulation results for ion transport related properties of a common solid polymer electrolyte have been assessed and discussed.